Translation of literary texts and online collaboration: Breaking barriers through virtual exchange - Maria da Conceição Emiliano Castel-Branco (University of Groningen Press, 2024)
Literary translation usually brings linguistic, textual, cultural, and pragmatic problems into perspective. As a knowledge-transfer process, it also demands a set of skills as the translator intends to convey, to some extent, the literary subtleties of the original. Graduate students attending a MA seminar of Translation of Literary Texts are frequently asked to undertake the process of translating a selection of excerpts of a variety of literary texts, to acknowledge difficulties and set up strategies for achieving their work. One of the most rewarding tools available to literary translators is working with the author, which is not always feasible in real-life activity and even more unlikely in Literary Translation classes. This report presents the practice of virtual exchange by describing the experience of matching Creative Writing students with students attending a Translation of Literary Texts seminar. Online collaboration gave Literary Translation students a sense of real-life experience by having the opportunity to communicate and work with the author, translating unpublished and untranslated texts. It was not only an opportunity of participating in a collaborative international project by means of virtual exchange, but also an opportunity of translating with the author.